A study of various neonatal outcomes and complications in live-born infants among IVF pregnancies - Yadav, Chetan; Yadav, Charu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: In-vitro fertilization or Assisted reproductive techniques (ART) is the most advanced technique of infertility treatment. In-vitro fertilization (IVF) has helped couples all over the world. However, the use of IVF has raised significant concern about the outcome of resulting pregnancies and the health of the newborns. There is a range of possible factors associated with the treatment that may contribute to potential adverse outcomes. Thus, the study was conducted to analyze the neonatal outcomes of children born by ART in the Indian context. Methods: The neonatal characteristics and complications of the live-born infants through IVF at Army Hospital R and R were analyzed in this study between March 2019 to February 2020. Results: Total 231 babies were born to the study group cases. 126 (54.54%) were singletons, 102 (44.16%) were of twin pregnancies and 1.3% were triplets. There were 65.36% term and 34.63% preterm. Of the 231 IVF neonates, 58 needed neonatal intensive care. There were 219 (94.8%) survivors, while 12 (5.2%) did not survive a week. The 16 (6.92%) survivors needed readmissions mainly due to hyperbilirubinemia. There were 106 (45.8%) babies whose weight was less than 2 kg. Conclusions: Infertility cases are usually older, and this is one reason for increased pregnancy and newborn infant complications. Neonates born through IVF appeared to be at higher risk of multiple births, prematurity, low birth weight, and other disabilities.